Využití kitu myRio pro měření a zpracování dynamických signálů - Heteš, Marek (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Táto práca sa zaoberá preskúmaním možností kitu myRIO a prostredia LabVIEW na záznam a spracovanie signálov z merania dynamických sústav a návrhom aplikácie v prostredí LabVIEW ktorá nám toto umožňuje. Koniec práce sa venuje testovaniu aplikácie a praktickej demonštrácii jej možností.

This thesis deals with research of options for data acquisition and signal analysis, of the myRIO kit and LabVIEW platform. Next it describes the design of application for data acquisition and signal analysis, and the last chapter of this thesis is about testing and a practical demonstration of our application.
Measurement and signal processing with myRio kit
Keywords: myRIO kit; LabVIEW; Záznam signálov; Analýza signálov; Vibrodiagnostika; myRIO kit; LabVIEW; Data acquisition; Signal analysis; Vibration diagnostics